Use of the Paid Open Access Option in Hybrid Open Access Journals in Agriculture: A Mixed-Methods Study. - Megan Kocher; Julie Kelly (Issues in Science and Technology Librarianship, 2016)
We explore the use and usefulness of the hybrid open access publishing model in agricultural sciences using a combination of quantitative and qualitative methods. To ascertain the level of usage of the paid open access option in hybrid open access journals in agriculture, we studied the agriculture-related journals published by six commercial publishers. These publishers offer authors the option of paying a fee, often close to $:000 per article, to make their article immediately freely available, usually with a Creative Commons license. We defined agriculture broadly but also assigned each journal to a subspecialty (e.g., animal science) in order to see if there were differences based on these subdivisions. For each journal we gathered data for 2014-2015 and noted the total number of research articles and the number of those that were made freely available by authors paying the open access fee. To give context to our results we also surveyed local faculty in agricultural sciences, asking their reasons for considering the paid open access options and the sources of the funds to pay for it. Survey respondents were asked about their academic position and rank to see if there were differences to be noted. We also investigated the findability of the open access articles, noting if each individual publisher offered a way to easily locate all the freely available articles in a particular journal and if there are other avenues to easily locate these articles. [ABSTRACT FROM AUTHOR]